Do older adults still choose comfortable cities? The quality of life and its affect on Indonesia’s older adult population - Subanti, Sri; Hakim, Arif Rahman; Rahmah, Mas; Riani, Asri Laksmi; Pratiwi, Hasih; Juansih, Juansih; Wibawa, Wahyu A. P. M.; Uktutias, Sendy A. M. (Frontiers in Public Health, 2025)
IntroductionMaintaining the quality of life for the aging urban population is becoming more and more crucial since this is becoming a global phenomenon. Cities need to be comfortable and accommodate facilities according to the needs of older adults to support the aging of the urban older adults while improving their quality of life. This paper aims to determine the value of a city’s quality of life in relation to its urban facilities and services, as well as to examine the relationship between quality of life and the aging population in Indonesian cities.MethodsThis study measures the quality of life using a hedonic model approach, which determines the price of each component of city comfort, both as facilities and services. We also employed an empirical model to investigate the relationship between quality of life and the aging population in Indonesian cities.ResultsOur research shows that the majority of Javan cities have high quality of life values because older residents have lived there for a long time, they can access facilities and services that meet their needs as they age.DiscussionThe quality of life plays an important role in the number of urban older adults, with health facilities, older adults-friendly transportation, security guarantees, and communication accessibility having a significant effect on the increase in urban older adults in Indonesia. The city governments should provide urban facilities that understand the characteristics and adjust to the needs of older adults.